2019
DOI: 10.3389/fonc.2019.01120
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus BART Long Non-coding RNAs Function as Epigenetic Modulators in Nasopharyngeal Carcinoma

Abstract: Epstein-Barr virus (EBV) establishes lifelong latent infection in humans and is associated with several lymphoid and epithelial cancers. In nasopharyngeal carcinoma (NPC), EBV expresses few viral proteins but elevated levels of Bam-HI A rightward transcripts (BARTs) RNA, which includes viral microRNAs and long non-coding RNAs (lncRNAs). BART lncRNAs localize within the nucleus of EBV-infected cells and knockdown of BART lncRNAs significantly affects the expression of genes associated with cell adhesion, oxidor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 35 publications
0
46
0
Order By: Relevance
“…In molecule research, EBV infection is an important cause of nasopharyngeal carcinoma (NPC) [ 56 ]. Whether EBV infection occurs in LELC is currently a concern.…”
Section: Discussionmentioning
confidence: 99%
“…In molecule research, EBV infection is an important cause of nasopharyngeal carcinoma (NPC) [ 56 ]. Whether EBV infection occurs in LELC is currently a concern.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of studies have demonstrated that dysregulated lncRNAs play an important role in the carcinogenesis, development and metastasis of different types of tumor (33)(34)(35). A number of lncRNAs have been reported to be associated with the recurrence, metastasis and resistance to adjuvant therapy of patients with BC (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Because of its nonspecific clinical manifestations, it is difficult to diagnose LELC before operation. EBV infection is an important cause of Nasopharyngeal carcinoma (NPC) [52] .…”
Section: Discussionmentioning
confidence: 99%